Differences in Daytime Activity Levels and Daytime Sleep Between Night and Day Duty: An Observational Study in Italian Orthopedic Nurses - Roveda, Eliana; Castelli, Lucia; Galasso, Letizia; Mulè, Antonino; Cè, Emiliano; Condemi, Vincenzo; Banfi, Giuseppe; Montaruli, Angela; Esposito, Fabio (Frontiers in Physiology, 2021)
Working nonstandard work schedules is often associated with increased sedentary behavior and risk of sleep disorders. Night shift workers are prone to accumulating sleep debt, which they recover by sleeping during the day. The effect on daytime activity levels is unknown. The present study aims to objectively assess whether daytime sleep could affect daytime activity levels of shift worker nurses, resulting in an accumulation of their activity debt differently between working and rest periods. The study population (N= 37; mean age 41.7 ± 9.1 years) was composed of orthopedic nurses working on a rotating schedule, including either a night shift (NS) or only day/afternoon shift (DS). Actigraph monitoring lasted both on the working and the rest period. For the NS nurses, the working period recorded higher daytime activity levels than the rest period, while daytime sleep during the working and rest periods was similar. Conversely, DS nurses showed higher daytime activity levels and shorter daytime sleep during the working period. NS nurses were less active than DS nurses during the working period, probably because NS tended to have a longer daytime sleep. During the rest period, daytime activity levels for both groups were decreased. For NS nurses, sleep recorded the better sleep parameters during the rest period, while sleep parameters did not show significant differences between the working and the rest periods in DS. During the working period, NS nurses slept worse than the DS nurses. Both groups tended to accumulate a debt in daytime activity levels during the rest period. While daytime sleep may be an excellent way to counteract sleep debt and increase sleep duration over 24 hour period, on the other hand, it makes nurses less active.